Multiculturalism in Music Education - Gorše, Kaja (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter highlights the importance of multiculturalism in music education, which fosters intercultural understanding and nurtures a sense of cultural diversity. Pupils should be introduced to music from various cultures at an early age, as this broadens their worldview and moves them beyond a focus on Western classical music. Through authentic materials and exposure to diverse musical practices, pupils develop cultural sensitivity. Teachers play a pivotal role in this process and must continually enhance their knowledge. The chapter also emphasizes the importance of providing pupils with opportunities to express themselves and connect with music, which helps build tolerance and reduce prejudice and stereotypes.